A Cross-Sectional Survey or Patients Perception and Knowledge Regarding Dental Implants in Pakistan - Ayesha Mehak Saeed, Saba Ahmed, Khadija Irshad, Mahnoor Haroon, Maria Naseer Khan, Shaban Ahmad Malik, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine the perception and knowledge regarding dental implants among patients admitted to hospital. Study Design: Cross-sectional/ Descriptive study Place and Duration: Islamic International Dental Hospital, Islamabad and Rawal Institute of Health Sciences, Islamabad for the duration of six months from September 2021 to February 2022. Methods: There were 160 patients of both genders were included in this survey. Presented patients had age between 18-70 years. After obtaining informed written consent, detailed demographics of each patient were recorded. Standardized self-explanatory questionnaires were given to patients during regular dental visits to assess their knowledge, source of information, and attitude about dental implants. SPSS 22.0 was used to analyze all data. Results: Among 160 cases, majority of the cases 90 (56.3%) were females and 70 (43.7%) were males. 27 (16.9%) were aged between 18-28 years, 25 (15.6%) had 29-38 years, 45 (28.1%) had age 39-48 years, 20 (12.5%) had age 49-60years and 43 (26.3%) had age >60 years. 42 (26.3%) had dental implants among all cases. There were 65 (40.6%) cases those were aware from the dental implants, among these dentists, friends and family members provided awareness. Dental implant therapy was most often described as being expensive, advance, and scary. Several of the individuals thought implants were painful and unsafe, although these perceptions were significantly less prevalent. Positive feedback was also received from patients in whom perception was high esthetic, improved mastication, no failures and high success rate. Conclusion: Most study respondents lacked dental implant competence. High cost prevents many from choosing dental implants. In developing nations like Pakistan, reducing costs would make dental implants more affordable for poor people. Keywords: Expensive, Dental Implants, Scary, Poor-socioeconomic status, Dental failures